Chemical fixation creates nanoscale clusters on the cell surface by aggregating membrane proteins - Ichikawa, Takehiko; Wang, Dong; Miyazawa, Keisuke; Miyata, Kazuki; Oshima, Masanobu; Fukuma, Takeshi (Communications biology, 2022)
Chemical fixations have been thought to preserve the structures of the cells or tissues. However, given that the fixatives create crosslinks or aggregate proteins, there is a possibility that these fixatives create nanoscale artefacts by aggregation of membrane proteins which move around freely to some extent on the cell surface. Despite this, little research has been conducted about this problem, probably because there has been no method for observing cell surface structures at the nanoscale. In this study, we have developed a method to observe cell surfaces stably and with high resolution using atomic force microscopy and a microporous silicon nitride membrane. We demonstrate that the size of the protrusions on the cell surface is increased after treatment with three commonly used fixatives and show that these protrusions were created by the aggregation of membrane proteins by fixatives. These results call attention when observing fixed cell surfaces at the nanoscale. Atomic force microscopy imaging shows that cell fixation can lead to unwanted aggregation of membrane proteins.